Influence of Laminar and Turbulent Flows on Heat Transfer in Liquid-Cooled Plate at Different Fin Arrangements - Abdul Majid, Fatin Fatihah; Irmawati Om, Nur; Hasini, Hasril (International Journal of Engineering and Technology, 2018)
This paper describes CFD investigation of flow and heat transfer in liquid cool plate of a lithium-ion battery. The work aims to compare the cooling performance of an LCP at different fin arrangement for both laminar and turbulence conditions. Prior to the extensive simulation works, the prediction of surface and liquid temperature is first compared made by conducting an experiment using one of the fin arrangement. Good agreement was obtained indicating the ability of the current model to simulate the flow and heat transfer of similar domain at different fin arrangement. The results indicated that the behaviour of the flow and heat transfer is different at laminar and turbulence conditions. The louvered find arrangement showed superior performance in terms of the enhancement of heat transfer. A combination of optimum configurations for fin arrangement and flow condition has enabled excellence overall heat transfer performance of the system.